3D Printing of “Liquid Wood” - Elena Puiu; Cristian Ursu; Dorin Vaideanu; Ion Sococol; Tudor-Cristian Petrescu; Alexandra Saviuc (Memoirs of the Scientific Sections of the Romanian Academy, 2022)
New research directions regarding novel materials and manufacturing processes are continuously developed all around the world. In particular, replacement products and materials exhibiting a high degree of recyclability and environmentally friendly are sought after in most activity fields. The goal of finding and eventually employing such materials in the immediate future is very important, if considering the massive invasion of plastic products, known as having an extremely long-term biodegradability and a still limited recycling capacity. “Liquid wood” is a material with potential to replace some plastic materials, due to its properties superior to other plastics and to its biodegradability. To this end, it is very important to know the properties of “liquid wood” and its processing possibilities, comparatively with plastic materials. The “liquid wood” granules considered for analysis are: arboform, arbofill and arboblend trademarks. The constituents of arboform granules are: lignocellulosic fibers (a combination of cellulose, lignin and wood polyoses); lignin, polyesters, as natural polymers; natural resins/ waxes: aromatic and aliphatic ketones, carbonic acids, alcohols, lactones and polycycles in monomeric, polymeric and oligomeric form. The arboblend granules contain biopolymers like polyester, polyhydroxialkanoate, ingeo TM, lignin, cellulose, starch, organic additives, natural resins or waxes and natural reinforcing fibers. Arbofill granules are mostly made of polypropylene or polyethylene as petrochemical polymers, reinforced with flax, hemp or wood fiber (natural fiber). As noticed, irrespective of the form of the “liquid wood” to be used for 3D printing, all have a significant content of lignin, therefore the experiments made for lignin are applicable. To obtain products for use in industry or even in everyday human activity, the material known as “liquid wood” has already been processed by injection molding in molds, by rotation and compression, compression, extrusion, thermoforming. The chemical methods employed involve hydroximethylation and epoxidation reactions, already used for obtaining lignin nanoparticles. As to the physical methods applied, a first one consists in the irradiation, in the ultrasonic field, of powder lignin (i.e., the sonicity method). A second physical way for obtaining “liquid wood” nanoparticles was by using laser ablation of the “liquid wood” in different liquid mediums. Generation of “liquid wood” nanoparticles through laser ablation has been experimentally and theoretically investigated. The dispersed ablation product resulted from the interaction of a nanosecond pulsed laser (Quantel Brilliant, 1064 nm, 10 ns) with an “liquid wood” target immersed in different liquid media has been studied through specific experimental techniques for morphological (atomic force microscopy – AFM, dynamic light scattering – DLS, transmission electron microscopy – TEM) and structural analysis (X-ray diffraction – XRD, Raman spectroscopy). The visible emitting regions of the plasma resulted from the interaction of a nanosecond pulsed laser with target material have been investigated through ICCD fast imaging. Additionally, a Langmuir probe has been used to study the transient charged particles cloud. A non-differentiable hydrodynamic model has been established according to our own experimental data.